2009
DOI: 10.1007/s12264-009-1125-7
|View full text |Cite
|
Sign up to set email alerts
|

Initial bradykinin triggers calcium-induced calcium release in C6 glioma cells and its significance

Abstract: Objective To investigate the underlying mechanism for the selective modulation of the permeability of blood-tumor barrier (BTB) by small dose of bradykinin (BK). Methods C6 glioma cells were treated with BK, and changes of intracellular nitric oxide (NO) and intracellular calcium level were measured with fluorescent spectrophotometer. Results The initial application of BK easily triggered extracellular calcium influx, which resulted in intracellular calcium store release in C6 glioma cells.The above mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Due to the presence of blood tumor barrier (BTB), macromolecular chemotherapeutic agents are arduous to reach the tumor tissues and dramatically attenuate the chemotherapeutic effect. Accordingly, selective BTB opening is an effective method to improve chemotherapeutic efficacy of brain glioma (Black and Ningaraj, 2004 ; Wang and Liu, 2009 ; Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of blood tumor barrier (BTB), macromolecular chemotherapeutic agents are arduous to reach the tumor tissues and dramatically attenuate the chemotherapeutic effect. Accordingly, selective BTB opening is an effective method to improve chemotherapeutic efficacy of brain glioma (Black and Ningaraj, 2004 ; Wang and Liu, 2009 ; Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In rat C6 glioma cells, bradykinin triggers Ca 2+ influx, resulting in calcium store Ca 2+ release, which is associated with nitric oxide generation for regulating permeability of blood‐tumour barrier,43 while in primary cultured rat brain microvascular endothelial cells, bradykinin‐triggered Ca 2+ influx‐induced Ca 2+ release is involved in regulation of the junction protein claudin‐5 19. A recent study shows that Ca 2+ signalling induced by bradykinin results from initial Ca 2+ release from ER IP3Rs followed by Ca 2+ entry through Ca 2+ release‐activated channels in normal pancreatic stellate cells 44.…”
Section: Discussionmentioning
confidence: 99%
“…41 However, an earlier study demonstrated that bradykinin induces an increase in inositol 1,4,5-triphosphate (IP3) in neonatal rat cardiomyocytes 42 and bradykinin-mediated short nocifensive responses is related to activating PLC, followed by Orai1 in afferent sensory neurons. 18 In rat C6 glioma cells, bradykinin triggers Ca 2+ influx, resulting in calcium store Ca 2+ release, which is associated with nitric oxide generation for regulating permeability of blood-tumour barrier, 43 while in primary cultured rat brain microvascular endothelial cells, bradykinin-triggered Ca 2+ influx-induced Ca 2+ release is involved in regulation of the junction protein claudin-5. 19 A recent study shows that Ca 2+ signalling induced by bradykinin results from initial Ca 2+ release from ER IP3Rs followed by Ca 2+ entry through Ca 2+ release-activated channels in normal pancreatic stellate cells.…”
Section: Ca 2+ Signalling By Bradykinin and Intracellular Signal Momentioning
confidence: 99%